Description, Taxonomy, and Comparative Genomics of a Novel species, Thermoleptolyngbya sichuanensis sp. nov., Isolated From Hot Springs of Ganzi, Sichuan, China - Tang, Jie; Li, Liheng; Li, Meijin; Du, Lianming; Shah, Md Mahfuzur R.; Waleron, Michal M.; Waleron, Malgorzata; Waleron, Krzysztof F.; Daroch, Maurycy (Frontiers in Microbiology, 2021)
Thermoleptolyngbya is a newly proposed genus of thermophilic cyanobacteria that are often abundant in thermal environments. However, a vast majority of Thermoleptolyngbya strains were not systematically identified, and genomic features of this genus are also sparse. Here, polyphasic approaches were employed to identify a thermophilic strain PKUAC-SCTA183 (A183 hereafter), isolated from hot spring Erdaoqiao, Ganzi prefecture, China. Whole-genome sequencing of the strain revealed its allocation to Thermoleptolyngbya sp. and genetic adaptations to the hot spring environment. Whilst the results of 16S rRNA were deemed inconclusive, the more comprehensive polyphasic approach encompassing phenetic, chemotaxic and genomic approaches strongly suggest that a new taxon Thermoleptolyngbya sichuanensis sp. nov. should be delineated around the A183 strain. The genome-scale phylogeny and average nucleotide/amino-acid identity confirmed the genetic divergence of the A183 strain from other strains of Thermoleptolyngbya along with traditional methods such as 16S-23S ITS and its secondary structure analyses. Comparative genomic and phylogenomic analyses revealed inconsistent genome structures between Thermoleptolyngbya A183 and O-77 strains. Further gene ontology analysis showed that the unique genes of the two strains were distributed in a wide range of functional categories. In addition, analysis of genes related to thermotolerance, signal transduction, and carbon/nitrogen/sulfur assimilation revealed the ability of this strain to adapt to inhospitable niches in hot springs and these findings were preliminarily confirmed using experimental, cultivation-based approaches.